Assessment and Comparison of Distress and Suicidal Behavior in Medical and Paramedical Students - Mitra Safa; Maryam Sadat Mirenayat; Mohsen Abedi; Atefeh Fakharian; Negin Ansari; Mahsan Norouz Afjeh; Farzaneh Haji Zadeh; Fatemeh Ghassem Boroujerdi (Journal of Social Behavior and Community Health, 2025)
Background: The sudden outbreak of coronavirus disease in 2019 resulted in major changes in  mental health of healthcare workers as the front line of fighting against thedisease. Medical students who were from the main members of healthcare workers suffered double pressure. The goal of current study was evaluation of suicidal behavior and psychological distress in medical and paramedical students to determine the mental health status of these students by identifying the mentioned factors. Methods: This is an applied, comparative and cross-sectional study. The sample members (302 participants) were selected by accessible method from medical students in Masih Daneshvari Hospital in 2023-2024. The Kessler Psychological Distress Scale (K6) and Suicide Behaviors Questionnaire-Revised (SBQ-R) were completed by all the participants. Data were analyzed by T, Chi square, Pearson and ANOVA tests by SPSS-22. Results: The highest and lowest risk of suicide was between interns (M=7.37) and fellowships (M=3.71), respectively. The highest and the lowest score of psychological distress was between interns (M=10.82)  and paramedical PhD students (M=6.9), respectively. Men had suicidal thought or attempt more than twice as likely as women (7.69% vs. 2.35%). The probability of suicide in future was more in men than women (1.53% vs. 0). There was a strong and significant (P ≤0.00) correlation between questions of suicidal behavior questionnaire and psychological distress. Conclusion: The higher scores of suicide and psychological distress of medical students in primary educational years, can reflect the high pressure volume, which they gain more compatibility, skill and ability for coping with the problems over time. By achieving the results of the current study, researchers would pay attention to psychological issues in healthcare workers, probable problems would be solved, and eventually, treatment of patients would done by more confidence